Copper Transporters and the Cellular Pharmacology of the Platinum-Containing Cancer Drugs - Howell, Stephen B. (American Society for Pharmacology and Experimental Therapeutics, 2010)
Multiple lines of evidence indicate that the platinum-containing cancer drugs enter cells, are distributed to various subcellular compartments, and are exported from cells via transporters that evolved to manage copper homeostasis. The cytotoxicity of the platinum drugs is directly related to how much drug enters the cell, and almost all cells that have acquired resistance to the platinum drugs exhibit reduced drug accumulation. The major copper influx transporter, copper transporter 1 (CTR1), has now been shown to control the tumor cell accumulation and cytotoxic effect of cisplatin, carboplatin, and oxaliplatin. There is a good correlation between change in CTR1 expression and acquired cisplatin resistance among ovarian cancer cell lines, and genetic knockout of CTR1 renders cells resistant to cisplatin in vivo. The expression of CTR1 is regulated at the transcriptional level by copper via Sp1 and at the post-translational level by the proteosome. Copper and cisplatin both trigger the down-regulation of CTR1 via a process that involves ubiquitination and proteosomal degradation and requires the copper chaperone antioxidant protein 1 (ATOX1). The cisplatin-induced degradation of CTR1 can be blocked with the proteosome inhibitor bortezomib, and this increases the cellular uptake and the cytotoxicity of cisplatin in a synergistic manner. Copper and platinum(II) have similar sulfur binding characteristics, and the presence of stacked rings of methionines and cysteines in the CTR1 trimer suggest a mechanism by which CTR1 selectively transports copper and the platinum-containing drugs via sequential transchelation reactions similar to the manner in which copper is passed from ATOX1 to the copper efflux transporters.